RECONSTRUCTING HISTORICAL LITERACY: STUDENTS’ PERSPECTIVES ON AI GENERATED CROSSWORD MEDIA BY CANVA AI FEATURE - Al Kamil, Muhammad Shofiyulloh (International Journal of Instructions and Language Studies, 2026)
The integration of Artificial Intelligence (AI) in history education offers opportunities to enhance students’ literacy skills, particularly in Islamic boarding school, pesantren, contexts where instruction is often lecture-centered and text-heavy. Despite growing research on digital game-based learning, limited studies have explored AI-generated crossword pedagogy in historical subjects from students’ perspectives. This study addresses three questions: (1) How does AI-generated crossword learning through Canva AI features influence students’ historical literacy? (2) What are students’ perspectives toward its implementation? (3) What benefits and challenges are experienced? This research employed a qualitative case study design conducted in a Madrasah Aliyah in Pasuruan, East Java. Eighteen students from Grades X–XII were selected through random sampling. Data were collected through semi-structured interviews (30–60 minutes) and analyzed using thematic analysis. Findings reveal three major results. First, 15 of 18 students reported increased engagement and motivation compared to traditional lectures. Second, 14 students indicated improved vocabulary retention, recall accuracy, and understanding of historical terms through retrieval practice embedded in crossword activities. Third, although 16 students expressed positive attitudes toward the innovation, challenges included unstable internet access (7 students) and initial unfamiliarity with Canva AI features (6 students). Several participants noted that crossword activities effectively reinforced terminology but required teacher explanation for deeper historical analysis. In conclusion, AI-generated crossword puzzles positively support micro-level historical literacy and classroom engagement but function best as complementary tools within varied instructional strategies.